Selfie Phenomenon in Muhammadiyah University of Sidoarjo (Phenomenology Approach Study) - Moch Muqhir (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Selfie itself is a form of photographs which is resulted from taking self-portraits that are indeed becoming a phenomenon for the wider community. The selfie phenomenon is currently one of the most booming phenomena at the end of 2013 until now, and certainly one of the readers often does this. The tradition of phenomenology is a tradition that is quite interesting to discuss, phenomenology may be said to reject the theory. This study focuses more on how the presentation of Culture selfie in Indonesia and how the Selfie Phenomenon in the Islamic view. In order to provide knowledge to adolescents and the public about the phenomenon of selfie among the people today. This study uses a phenomenological approach, which is defined as a study in the field of philosophy that studies humans as a phenomenon. The tradition of phenomenology places very strong emphasis on the perceptions and interpretations of human subjective experience. This research has used the elaboration of methods and steps carried out by explorative in describing them using a qualitative approach. This research method used is a qualitative research method, the technique of collecting samples uses the method of exposure to find the research focus about selfie phenomenon in Muhammadiyah University in Sidoarjo. This phenomenon of selfie happened because of the technological developments were so extraordinary. If in the past the photos of self were not possible because of the lackness of capable and supportive technology, now there are many tools that support such as gadgets or cell phones for selfies. Keywords: selfie phenomenon, society, university, Muhammadiyah, approach, phenomenology, technology, photo